O020 What helped you and what prevented you from getting good sleep? Contribution of daily facilitators and barriers to adolescent sleep. (7th October 2021) - Maskevich, S; Shen, L; Wiley, J; Drummond, S; Bei, B
Abstract: Introduction: This intense longitudinal study examined factors that facilitate and hinder sufficient and good quality sleep in adolescents' everyday life. Methods: 205 (54.2% female, 64.4% non-white) Year 10–12 adolescents (Mage = 16.9 ± 0.9) completed daily morning surveys and wore actigraphy over 2 school-weeks and 2 subsequent vacation-weeks. Morning surveys assessed self-reported sleep and the usage of 8 facilitators and 6 barriers of sleep from the previous night. Linear mixed-effects models examined contribution of facilitators/barriers to actigraphy and self-reported total sleep time (TST) and sleep onset latency (SOL), controlled for age, sex, race, place of birth, and study day. Schooldays/non-schooldays was included as a moderator. Results: Seven facilitators and two barriers were endorsed by high proportions (>30%) of adolescents as frequently (≥50% days) helping/preventing them from achieving good sleep. Facilitators predicting longer TST and shorter SOL, were: "follow body cues", "manage thoughts and emotions", "create good sleep environment", "avoid activities interfering with sleep" and "plan bedtime and go to bed as planned" (only TST on schooldays). Barriers predicting shorter TST and longer SOL, were: "pre-bedtime thoughts and emotions", "unconducive sleep environment", "activities interfering with sleep", "inconsistent routines" and "other household members' activities". Overall, facilitators or barriers explained an additional 1–5% (p-values < .001) of variance beyond the covariates. Discussion: Adolescents perceive a range of factors as facilitating and as preventing sufficient and good quality sleep in everyday life. These factors are predictive of their sleep duration and onset latency, and need further research to understand their functions and clinical implications.